Structure and evolution of flux transfer events near dayside magnetic reconnection dissipation region: MMS observations. Issue 12 (29th June 2017) - Dong, X.‐C.; Dunlop, M. W.; Trattner, K. J.; Phan, T. D.; Fu, H.‐S.; Cao, J.‐B.; Russell, C. T.; Giles, B. L.; Torbert, R. B.; Le, Guan; Burch, J. L.
Abstract: We investigate a series of three small‐scale flux transfer events (FTEs) associated with reconnected flux ropes, recently generated by a nearby, dayside magnetic reconnection line. The data are observed by the Magnetospheric Multiscale spacecraft near noon local time. We find that the associated FTEs are created by secondary magnetic reconnection and have different magnetic field topologies, which is a similar condition to that expected in the multiple X‐line magnetic reconnection (MR) model. The calculated results show that the sizes of the FTEs become larger with the time elapsed and the MR reconnection jets at the FTEs are all located on the trailing and outer edges. The above features indicate that these FTEs are still in the evolutionary stage after they are ejected from the reconnection region. Our observations suggest that mesoscale or even typical size FTEs can be created from secondary MR, initially, and subsequently can evolve to a typical size in the process of spreading. Key Points: A series of (three) ion‐scale FTEs are observed within 1 min before MMS crosses the magnetopause reconnection dissipation region These FTEs are created by secondary magnetic reconnection and still in the evolution stage after they are ejected from reconnection region These FTEs appear to be associated with secondary MR reconnection but have different magnetic field topologies